A national security imperative : protecting Singapore businesses from cyber-espionage - Yilmaz, Senol (2014)
Cyber-espionage is a real and growing threat to businesses and economies. Some counter-measures can be taken by the private sector. But the government plays an important role in protecting its businesses from cyber-exploitation.